2010
DOI: 10.1590/s1413-35552010000600002
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Systems: constraints approach to rehabilitation

Abstract: Background: Classification systems (Nagi, International Classification for Function [ICF]) have become popular for categorizing the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 81 publications
1
23
0
3
Order By: Relevance
“…We wanted our findings to be representative for the real-life environments (Dingenen & Gokeler, 2017), hereby acknowledging the importance of the environmental and task constraints within the dynamic system theory (Davids et al, 2003;Holt, Wagenaar, & Saltzman, 2010). We used a portable movement analysis system in a gym to assess spinal alignment in the thoracolumbar and lumbopelvic areas during the lifts.…”
Section: Instruments and Measurementsmentioning
confidence: 99%
“…We wanted our findings to be representative for the real-life environments (Dingenen & Gokeler, 2017), hereby acknowledging the importance of the environmental and task constraints within the dynamic system theory (Davids et al, 2003;Holt, Wagenaar, & Saltzman, 2010). We used a portable movement analysis system in a gym to assess spinal alignment in the thoracolumbar and lumbopelvic areas during the lifts.…”
Section: Instruments and Measurementsmentioning
confidence: 99%
“…In sports medicine, proponents of dynamic systems theory of motor behavior suggest that interventions surrounding training and rehabilitation should foster functional variability within the movement system to promote patterns that can adapt to changing task, environmental, and individual constraints. 24,25,[36][37][38] Results from this study showed that ankle bracing elicited acute adaptations of coordination pattern dynamics, characterized by diminished functional variability of the lower-extremity. Thus, clinicians should be aware of the potential barriers that ankle bracing may present in situations where functional variability is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Note that this reduced multifractality remains different from corresponding surrogates. Hence, nonlinear interactions across scales can constrict movement variability, making reduced multifractality more adaptive [63][64][65]. This distinction is a departure from any shorthand presumption that 'more multifractal is better' supported by early studies of heart rate variability (HRV) [66].…”
Section: Discussionmentioning
confidence: 99%